Design and improvement of dynamic performance of solar-powered BLDC motor for electric vehicles in agricultural applications - Savitri Medegar; M. Sasikala (Institute of Advanced Engineering and Science, 2026)
One of the most pressing environmental problems is the rapid increase in the production of greenhouse gases by transportation vehicles. This paper looks into SPEVs, or solar-powered electric vehicles. The answer to the problems of transportation-related pollution and fuel usage. In an electric vehicle, the power comes from a battery that may be charged by solar panels or any other external power source. By making use of the perturb and observe (P&O) maximum power point tracking (MPPT) controller, one can achieve maximum power. The DC voltage that the photovoltaic module produces is amplified when it is fed into a voltage source inverter (VSI) via this enhanced output. The tool for the job here is a buck-boost converter. To power their wheels, EVs rely on brushless direct current (BLDC) motors and variable speed inverters (VSIs), which transform DC power from solar panels into AC power. We compare the efficiency of electric vehicles (EVs) attained by raising converter voltages and battery state of charge (SoC) using a PI controller, and we look at the performance of photovoltaic (PV) and brushless linear direct current (BLDC) motors. We use MATLAB/Simulink to do the validation.